Mating and Reproductive Success in Free-Ranging Stump-Tailed Macaques: Effectiveness of Male–Male Coalition Formation as a Reproductive Strategy - Toyoda, Aru; Maruhashi, Tamaki; Kawamoto, Yoshi; Matsudaira, Kazunari; Matsuda, Ikki; Malaivijitnond, Suchinda (Frontiers in Ecology and Evolution, 2022)
Male coalition-like formation, recently found in stump-tailed macaques (Macaca arctoides), occurs when several top-ranking males collaboratively guard females to prevent mating with other rival males and actively share secured mating opportunities with their allies. We lack a comprehensive understanding of the proximate mechanisms underlying such male coalitions, e.g. the effect of genetic relatedness. Such cooperative partner choice among males is particularly interesting in animals, such as M. arctoides, that live in matrilineal (female philopatry/male dispersal) society. Theoretically, in such a social system, females, and not males, are often related to each other by kinship. Thus, the occurrence of cooperative behavior between related females are generally common, but it would be rare between unrelated/non-kin males in such matrilineal society. Herein, for the first time, we report detailed copulatory behaviours, including mating and reproductive success, in relation to male coalition-like formation in free-ranging M. arctoides following direct behavioural observation and genetic analysis. We found that coalition-forming male–male alliances often occur among both individuals that are highly related and those that are less related. We identified two groups with different mating strategies, i.e. single-male monopoly and coalition-male monopoly groups. In both groups, nearly 80% of copulations were monopolised by a single male or by coalition males. However, the single-male monopoly strategy allows opportunistic/sneaky copulations by other males with a relatively high probability. Thus, the degree of reproductive success did not reflect mating success. In contrast, the males employing a coalition strategy successfully shared their mating and reproductive success, particularly in the largest group. Compared with single-male monopolised groups, the coalition-male monopoly groups copulated with a considerably more number of females, suggesting that coalition males can effectively guard against opportunistic/sneaky copulation by rival males. We also found that coalition-forming male–male alliances often occur regardless of the degree of kinship/relatedness, indicating the complexity and flexibility inherent in the male social bond of M. arctoides.